Complex cytogenetic rearrangements at the DURS1 locus in syndromic Duane retraction syndrome. Issue 1 (30th September 2013) - Baris, Hagit N.; Chan, Wai‐Man; Andrews, Caroline; Behar, Doron M.; Donovan, Diana J.; Morton, Cynthia C.; Ranells, Judith; Pal, Tuya; Ligon, Azra H.; Engle, Elizabeth C.
Key Clinical Message A patient with syndromic Duane retraction syndrome harbors a chromosome 811.1q13.2 inversion and 8p11.1‐q12.3 marker chromosome containing subregions with differing mosaicism and allele frequencies. This case highlights the potential requirement for multiple genetic methods to gain insight into genotype–phenotype correlation, and ultimately into molecular mechanisms that underlie human disease.